A companion to American indie film - King, Geoff, 1960- (Malden, MA : Wiley Blackwell, 2016)
A Companion to American Indie Film features a comprehensive collection of newly commissioned essays that represent a state-of-the-art resource for understanding key aspects of the field of indie films produced in the United States. -Takes a comprehensive and fresh new look at the topic of American indie film -Features newly commissioned essays from top film experts and emerging scholars that represent the state-of-the-art reference to the indie film field -Topics covered include: indie film culture; key historical moments and movements in indie film history; relationships between indie film and other indie media; and issues including class, gender, regional identity and stardom in in the indie field -Includes studies of many types of indie films and film genres, along with various filmmakers and performers that have come to define the field.
Introduction / Geoff King -- Indie Culture. Indie Film as Indie Culture / Michael Z Newman -- The Making of the Indie Scene / Sherry B Ortner -- Indie as Organic / Geoff King -- Indie and Other Media. Quirky Culture / James MacDowell -- Independent Intersections / Jamie Sexton -- Post-Cinema Soderbergh / Mark Gallagher -- Criticism, Marketing, and Positioning Indie. Structuring Indie and Beasts of the Southern Wild / Erin Pearson -- Marketing American Indie in the Shadow of Hollywood / Finola Kerrigan -- Movements/Moments. Proto-Indie / Janet Staiger -- From Independent to Indie / Yannis Tzioumakis -- Going Mainstream / Thomas Schatz -- Looking through a Rearview Mirror / JJ Murphy -- Indie as Regional. The Pull of Place / Mary P Erickson -- Rural Crimewave / John Berra -- Aesthetics and Politics. Life During Wartime / Claire Perkins -- Indie Cinema and the Neoliberal Commodification of Creative Labor / Claire Molloy --'They Believe Every Fuckin' Word Because You're Super Cool' / Stella Bruzzi -- The Craft of Independent Filmmaking / Warren Buckland -- Kickstarting Indie. Crowdfunding, Independence, Authorship / Chuck Tryon -- Go Digital or Go Dark / Sarah ES Sinwell -- Indie Acting and Stardom. Casing Indie Acting / Chris Holmlund -- Flexible Stardom / Paul McDonald.
Includes index.
Print version record.
Keywords: Independent films -- United States -- History and criticism; Independent films -- Production and direction -- United States; Independent filmmakers -- United States; Electronic books; Electronic books